2020
DOI: 10.3390/polym12081674
|View full text |Cite
|
Sign up to set email alerts
|

PEG/PPG-PDMS-Adamantane-Based Crosslinked Terpolymer Using the ROMP Technique to Prepare a Highly Permeable and CO2-Selective Polymer Membrane

Abstract: In this study, precursor molecules based on PEG/PPG and polydimethylsiloxane (PDMS), both widely used rubbery polymers, were copolymerized with bulky adamantane into copolymer membranes. Ring-opening metathesis polymerization (ROMP) was employed during the polymerization process to create a structure with both ends crosslinked. The precursor molecules and corresponding polymer membranes were characterized using various analytical methods. The polymer membranes were fabricated using different compositions of PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The P15 membrane, with its high TEOS concentration, shows a fully crosslinked structure when compared to the P9 and P12. Moreover, the crosslinking structure of the PDMS membrane can induce high solution diffusion for CO 2 /N 2 separation [ 47 ]. Therefore, higher selectivity was observed for the P15 membranes, owing to their crosslinked structure.…”
Section: Resultsmentioning
confidence: 99%
“…The P15 membrane, with its high TEOS concentration, shows a fully crosslinked structure when compared to the P9 and P12. Moreover, the crosslinking structure of the PDMS membrane can induce high solution diffusion for CO 2 /N 2 separation [ 47 ]. Therefore, higher selectivity was observed for the P15 membranes, owing to their crosslinked structure.…”
Section: Resultsmentioning
confidence: 99%
“…Metathesis polynorbornenes, as a rule, are less permeable and less stable chemically and thermally due to the presence of double bonds in their backbone. Recently, the post-modification of metathesis polynorbornenes was suggested to adjust their gas separation properties and improve their thermochemical stability [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The proposed modification routes included hydrogenation [ 4 , 11 ], epoxidation [ 3 ], gem -difluorocyclopropanation [ 5 ], and cross-linking [ 6 , 7 , 8 , 9 , 10 ] of the double bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the post-modification of metathesis polynorbornenes was suggested to adjust their gas separation properties and improve their thermochemical stability [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The proposed modification routes included hydrogenation [ 4 , 11 ], epoxidation [ 3 ], gem -difluorocyclopropanation [ 5 ], and cross-linking [ 6 , 7 , 8 , 9 , 10 ] of the double bonds. It was shown that the epoxidation led to a significant decrease in gas permeability of metathesis polynorbornenes due decreases in diffusion and solubility coefficients for almost all gases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These materials are used as functional materials for the microelectronic, aerospace, electrical insulating and semiconductor industries. Another promising area developed over the last decade is the synthesis of polymer membranes used as gas separation systems and fuel cells [8,9]. The presence of cardo groups in the polymer membrane significantly affects their gas permeable characteristics due to the packing density and segmental mobility of the polymer chain.…”
Section: Introductionmentioning
confidence: 99%